Non-pharmacological Approaches to Treatment of Patients over 60 Years as a Way to Improve Pharmacotherapy Safety and Prevent Polypharmacy - A. P. Pereverzev; O. N. Tkacheva; Yu. V. Kotovskaya; Yu. S. Onuchina; E. N. Dudinskaya; A. V. Naumov (Безопасность и риск фармакотерапии)
Abstract. The demographic aging of the population of the earth observed in recent years is associated, inter alia, with the advent of new effective and safe medicines. However, the availability of highly effective drugs on the market also has a reverse side — the appearance of adverse drug reactions (ADRs), in particular as a result of drug-drug interactions. The use of non-pharmacological methods of treatment and prevention of diseases seems particularly relevant for patients of the older age group, as it allows not only to reduce the drug burden, to reduce the risk of ADRs but also to improve the patient’s state in case of diseases that have no effective pharmacotherapy and pharmacological prophylaxis. The aim of the study was to systematize and analyze data on non-pharmacological treatment methods in order to increase the safety of pharmacotherapy and prevent polypragmasia in elderly patients by informing health care providers about non-drug methods of correcting significant geriatric problems. The approaches to the correction of some major geriatric problems (delirium, sarcopenia, pain syndrome), including cognitive training, physical activity, diet, frequent reorientation of patients, placement of patients in specially equipped rooms («delirium room») were presented. The use of non-pharmacological approaches can significantly improve the safety of drug therapy, reduce the risks of ADRs, improve the patient’s prognosis and quality of life, and also effectively prevent polypharmacy.